SBA-15-oxynitrides as a solid-base catalyst: effect of nitridation temperature on catalytic activity - Singh, Baljeet; Mote, Kaustubh R.; Gopinath, Chinnakonda S.; Madhu, Perunthiruthy K.; Polshettiwar, Vivek (Angewandte Chemie-International Edition, 2015)
Solid bases, such as SBA-15-oxynitrides, have attracted considerable interest for potential applications as catalysts in important industrial processes. Reported herein is that by simply tuning the temperature of nitridation (ammonolysis), the catalytic activity of these solid bases can be enhanced. Solid-state NMR spectroscopy and XPS studies provided the reasoning behind this change in activity.
Keywords: heterogeneous catalysis; Nanostructures; NMR spectroscopy; photoelectron spectroscopy; solid-state structures